An intracerebroventricular injection of amyloid-beta peptide (1–42) aggregates modifies daily temporal organization of clock factors expression, protein carbonyls and antioxidant enzymes in the rat hippocampus - Navigatore Fonzo, Lorena Silvina (2021)
Alzheimer disease (AD) is the most frequent form of dementia in the elderly. It is characterized by the deterioration of memory and learning. The histopathological hallmarks of AD include the presence of extracellular deposits of amyloid beta peptide, intracellular neurofibrillary tangles, neuron and synapse loss, in the brain, including the hippocampus. Accumulation of Aβ peptide causes an increase in intracellular reactive oxygen species (ROS) and free radicals associated to a deficient antioxidant defense system. Besides oxidative stress and cognitive deficit, AD patients show alterations in their circadian rhythms. The objective of this work was to investigate the effects of an intracerebroventricular injection of amyloid beta peptide Aβ(1–42) aggregates on temporal patterns of protein oxidation, antioxidant enzymes and clock factors in the rat hippocampus. Four-month-old male Holtzman rats divided into the groups control (CO) and Aβ-injected (Aβ), were maintained under 12 h-light12h-dark conditions and received water and food ad-libitum. Hippocampus samples were isolated every 6 h during a 24 h period. Our results showed daily patterns of protein carbonyls, catalase (CAT) and glutathione peroxidase (GPx) expression and activity, as well as Rorα and Rev-erbß mRNA, in the rat hippocampus. Interestingly, an intracerebroventricular injection of Aβ aggregates modified daily oscillation of protein carbonyls levels, phase-shifted daily rhythms of clock genes and had a differential effect on the daily expression and activity of CAT and GPx. Thus, Aβ aggregates might affect clock-mediated transcriptional regulation of antioxidant enzymes, by affecting the formation of BMAL1:CLOCK heterodimer, probably, as a consequence of the alteration of the redox state observed in rats injected with Aβ.